The negative association between the docosapentaenoic acid intake and the incidence of AMD based on NHANES 2005–2008 - Xu, Baiwei; Hu, Yi; Di, Jie; Liu, Zhongwei; Yu, Ziyan; Han, Lin; Ning, Yuan (Frontiers in Nutrition, 2024)
Introduction Age-related macular degeneration (AMD) is an ophthalmic disease that causes visual impairment and is one of the leading causes of blindness in the elderly. Fatty acids are essential nutrients required by the body and play a cornerstone role in the life activities of the body. Many studies have reported that fatty acids are involved in the development of AMD. To confirm this association, we conducted the present study. Methods We analyzed the association between all fatty acid intake and AMD using National Health and Nutrition Examination Survey (NHANES) data from 2005–2008. Quantile regression was performed to assess the effect of fatty acids on AMD at different intake levels. Results After adjusting for covariates, only saturated fatty acids showed no significant difference between AMD patients and non-AMD patients (23.64 g vs. 26.03 g, p = 0.052). Total fat (70.88 g vs. 78.86 g, p = 0.024), monounsaturated fatty acids (25.87 g vs. 28.95 g, p = 0.019), polyunsaturated fatty acids (15.10 g vs. 17.07 g, p = 0.017) showed significant differences between the two groups. When AMD was considered as an outcome, the association between AMD and docosaentaenoic acid (DPA) was negative in the multivariate logic model (model 1: OR = <0.001, 95% CI = <0.001 0.734; model 2: OR = <0.001, 95% CI = <0.001 0.002; model 3: OR = <0.001, 95% CI = <0.001 0.002). In the quantile regression, DPA was shown to be negatively associated with the presence of AMD only in the fourth quartile in model 2 and model 3 (model 2: OR = <0.001, 95% CI = <0.001 0.927; model 3: OR = <0.001, 95% CI = <0.001 0.775). Discussion Therefore, based on above results, we concluded that DPA intake could prevent the development of AMD.